Bone Mineral Density in Postmenopausal Women Heterozygous for the C282Y HFE Mutation - Jenny E. Gunton; Frances Gates; Greg R. Fulcher; Phillip B. Clifton-Bligh (Journal of Osteoporosis)
Mutations in the HFE gene may be associated with increased tissue iron stores reflected in an elevated serum ferritin. With homozygous mutation C282Y, the increase in serum ferritin may be associated with tissue damage in the liver, pancreas, and pituitary and with a reduced bone mineral density. With heterozygous mutation C282Y, the degree of iron retention is less but information relating to how a heterozygous C282Y mutation might impact bone mineral density is uncertain. The present study was undertaken to study the relationships between bone mineral density measured by dual energy X-ray absorptiometry and the serum ferritin and serum iron in postmenopausal women heterozygous for the C282Y mutation. The spinal bone mineral density, L2–4, was significantly less than age matched community controls (P=0.016). There was no significant change in the femoral neck bone mineral density compared to age matched community controls. The correlation between the spinal bone mineral density, L2–4, the femoral neck bone mineral density, and the serum ferritin was not significant. The serum iron correlated significantly inversely with the femoral neck bone mineral density (P=0.048). The heterozygous C282Y mutation may be associated with impairment of bone cell function in postmenopausal women when only small increases in the serum iron or serum ferritin have occurred.